2010
DOI: 10.1002/smll.201000448
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Carpets

Abstract: The fabrication of defined polymer objects of reduced dimensions such as polymer-coated nanoparticles (zero-dimensional (0D)), cylindrical brushes (1D), and polymer membranes (2D), is currently the subject of intense research. In particular, ultrathin polymer membranes with high aspect ratios are being discussed as novel materials for miniaturized sensors because they would provide extraordinary sensitivity and dynamic range when sufficient mechanical stability can be combined with flexibility and chemical fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 42 publications
3
67
0
1
Order By: Relevance
“…The synthesis, processing and characterization of such complex brush structures, for example, mixed brushes [193][194][195][196][197], multiblock copolymer brushes [114,115,198], gradient polymer brushes [199,200], nanopatterned polymer brushes [107,116], polymer carpet/Janus membrane [8,[201][202][203] and polymer nanochannels [114,117] are of great interest from a fundamental as well as technological perspective. Comprehensive understanding of structure-property relationships in well-defined and fully characterized polymer brushes aided by new synthesis as well as predictive modeling can open up newer applications for polymer brushes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis, processing and characterization of such complex brush structures, for example, mixed brushes [193][194][195][196][197], multiblock copolymer brushes [114,115,198], gradient polymer brushes [199,200], nanopatterned polymer brushes [107,116], polymer carpet/Janus membrane [8,[201][202][203] and polymer nanochannels [114,117] are of great interest from a fundamental as well as technological perspective. Comprehensive understanding of structure-property relationships in well-defined and fully characterized polymer brushes aided by new synthesis as well as predictive modeling can open up newer applications for polymer brushes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the crosslinking of these brushes to create membranes is relatively new. For example, if the stimuli-responsive nature of the polymer brushes (e.g., to pH or temperature) needs to be preserved, crosslinking the brushes is not an option as the responsiveness is compromised, instead alternate approaches based on "polymer carpets" have been developed [8,9]. The term polymer carpets was recently coined to refer to free-standing polymer brushes, grafted from a crosslinked monolayer of self-assembled initiators following photo-polymerization of suitable monomers.…”
Section: Introductionmentioning
confidence: 99%
“…21 Apart from that the terminal functionality of CNMs is inherited from the precursor molecules but can be modified upon electron irradiation, e.g., nitro group converts to amino group, 22 which enables further molecular grafting onto aminoterminated regions. 23,24 Mechanical properties of CNMs have been characterized by bulge testing in an atomic force microscope (AFM bulge test) 25 and it was found that their Young's moduli can also be tailored in the range of 10-20 GPa, depending on the precursor molecules. 26 In contrast to graphene being a semimetal, the pristine CNMs are dielectric and structurally amorphous but can be converted to well-conducting nanocrystalline graphene upon thermal annealing.…”
mentioning
confidence: 99%
“…On the other hand, the preparation of quasi-2D polymers either requires the undesirable crosslinking of the materials, using expensive and opaque novel metal supports, or high-energy electron beams. 16,17 Therefore, the investigation of the fundamental properties as well as practical applications of these organic 2D materials have remained largely hindered.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the preparation of quasi-2D polymers either requires the undesirable crosslinking of the materials, using expensive and opaque novel metal supports, or high-energy electron beams. 16,17 Therefore, the investigation of the fundamental properties as well as practical applications of these organic 2D materials have remained largely hindered.In this paper, we report the development of a new type of functional organic 2D material, namely 'polymer@graphene 2D objects' , which are prepared in a cost-effective and high-throughput manner. Polymer@graphene 2D objects are made of functional…”
mentioning
confidence: 99%